Structural Drivers of Corporate Resilience during Economic Crises: An ISM–MICMAC Approach - Yanti Budiasih; Irma Novida; Marifatul Hikmah (MIX: JURNAL ILMIAH MANAJEMEN, 2026)
Economic crises have repeatedly exposed firms’ vulnerabilities in absorbing shocks, adapting to adverse conditions, and restoring performance. Corporate resilience has therefore become a critical concept in understanding firms’ ability to survive and recover during periods of economic disruption. However, existing studies largely examine resilience determinants in isolation, offering limited insight into their structural and hierarchical interdependencies.Objectives: This study aims to examine corporate resilience during economic crises by adopting a structural perspective that recognizes the interdependencies among key resilience determinants and identifies their hierarchical roles within an integrated system.Methodology: This study adopts a qualitative structural research design using Interpretive Structural Modeling (ISM) combined with MICMAC analysis. Twelve determinants of corporate resilience were identified through an extensive literature review and validated by expert judgment involving academics and finance practitioners.Findings: The results show that liquidity and buffer capacity function as foundational driving factors enabling financial flexibility, which serves as an intermediate structural mechanism. Stability and adaptability act as linkage mechanisms that translate financial capacity into operational continuity, while recovery performance emerges as a dependent outcome. The absence of autonomous variables indicates that all determinants are structurally interconnected.Conclusion: The study concludes that corporate resilience during economic crises should be strengthened through a layered and sequential approach rather than isolated improvements in individual indicators, emphasizing the importance of aligning financial and operational mechanisms according to their structural roles. Keywords: Corporate resilience; Financial flexibility; Liquidity management; Crisis management; Interpretive Structural Modeling (ISM)